Teaching Strategies to Help EAP Learners - Wilder, Paula (My University, 2012)
Although English grammar and mechanics do pose problems for EAP learners, one of the greatest challenge these learners face rests with the cultural differences in the organizational expectations of an academic essay. Specific teaching strategies exist, such as pre-writing, revising, and providing feedback, which will not invalidate other cultures but help students overcome cultural writing barriers.
Keywords: EAP learners; Education; TALGS